Immunization with pVAXhsp65 Decreases Inflammation and Modulates Immune Response in Experimental Encephalomyelitis - Goncalves Zorzella-Pezavento, Sofia Fernanda [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; Donega Franca, Thais Graziela [UNESP]; Watanabe Ishikawa, Larissa Lumi [UNESP]; Martins, Douglas Rodrigues [UNESP]; Silva, Celio Lopes; Sartori, Alexandrina [UNESP] (Karger, 2010)
Background: A DNA vaccine (pVAXhsp65) containing the gene of a heat-shock protein (hsp65) from Mycobacterium leprae showed high immunogenicity and protective efficacy against tuberculosis in BALB/c mice. A possible deleterious effect related to autoimmunity needed to be tested because hsp65 is highly homologous to the correspondent mammalian protein. In this investigation we tested the effect of a previous immunization with DNAhsp65 in the development of experimental autoimmune encephalomyelitis (EAE), a rat model of multiple sclerosis. Methods: Female Lewis rats were immunized with 3 pVAXhsp65 doses by intramuscular route. Fifteen days after the last DNA dose the animals were evaluated for specific immunity or submitted to induction of EAE. Animals were evaluated daily for weight loss and clinical score, and euthanized during the recovery phase to assess the immune response and inflammatory infiltration at the central nervous system. Results: Immunization with pVAXhsp65 induced a specific immune response characterized by production of IgG(2b) anti-hsp65 antibodies and IFN-gamma secretion. Previous immunization with pVAXhsp65 did not change EAE clinical manifestations (weight and clinical score). However, the vaccine clearly decreased brain and lumbar spinal cord inflammation. In addition, it downmodulated IFN-gamma and IL-10 production by peripheral lymphoid organs. Conclusion: Our data demonstrated that this vaccine does not trigger a deleterious effect on EAE development and also points to a potential protective effect. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Experimental autoimmune encephalomyelitis; Lewis rats; DNA vaccine; Tuberculosis; Heat-shock protein